Modelling the Fate of Chemicals in the Environment and the Human Body (The Handbook of Environmental Chemistry, 2018)
This volume focuses on modelling the fate of chemicals in the environment and the human body to arrive at an integrated exposure assessment. It covers five broad topics, namely: future challenges in exposure assessment; the evolution of human health and environmental risk assessment; standard documentation for exposure models; modelling different environmental components (i.e. surface waters, atmosphere, soil, groundwater, plants, aquatic organisms and mammals); and the fate of contaminants in humans. This work draws on the authors' and editors' extensive experience and a range of different research activities, including case studies, that have led to the development of MERLIN-Expo, a standardised software package for simulating the fate of chemicals in the main environmental systems and in the human body in an integrated manner. It will be of considerable interest to researchers and students, risk managers, and policy- and decision-makers whose work involves environmental protection and human health.